EFFECTS OF NUTRITION SUPPORT ON ATTAINMENT OF MOTOR SKILLS MILESTONES IN CHILDREN RECEIVING ANTIRETROVIRAL THERAPY (ART) IN SELECTED SLUMS OF NAIROBI, KENYA - Nkirote, Lucy; Ng'ang'a, Prof. Zipporah W.; Muchiri, Prof. Eric M.; Kombe, Dr. Yeri (Journal of Health, Medicine and Nursing, 2019)
Purpose: To assess effect of nutrition support on achievement of motor developmental milestones in HIV-infected children on ART in urban resource-poor settings of Nairobi, Kenya. Methodology: Quasi experimental study design, carried out in eight slum areas of Nairobi. Two hundred and sixty (260) HIV-infected children (aged 6-59 months) on ART were randomly selected from eight comprehensive care centres (CCCs) and followed for a period of up to six months. Findings: Nutritional support did not significantly contribute to attainment of neither gross motor (AOR=2.45; 95% CI: 0.81-7.46; P=0.114) nor fine motor skills milestones (AOR=1.08; 95% CI: 0.33-3.51; P=0.904) in HIV-infcted children. Unique contribution to theory, practice and policy: The study provides insights that are critical in enabling programmes providing support to HIV-infected children consider additional factors such as environmental, treatment and educational interventions to their nutrition interventions. The findings of study can also be used to inform policy with regard to effectiveness of interventions in concretely addressing care and management of HIV and AIDS among young children in general and in resource poor settings in particular.